Hubungan Tingkat Pengetahuan Kesehatan Reproduksi dengan Perilaku Seksual pada Remaja di SMA Negeri 1 Baturaden Kelas XI - Syifaul Rahman, Nadifah (Jurnal Kebidanan Harapan Ibu Pekalongan, 2025)
In Indonesia, reproductive health problems in adolescents are closely related to risky adolescent behavior. Based on the results of the 2020 survey, 55% of adolescents and 1% of women smoke, 15% of male adolescents and 1% of female adolescents use illegal drugs, 5% of male adolescents drink alcoholic beverages, and 8% of men and 1% of women have had sexual intercourse while dating. And there are women who get pregnant under the age of 21, namely 14,15,16 years old are already pregnant, many under 21 years old do not understand that getting married at that age can cause infant mortality and bleeding. This study aims to determine the relationship between the level of knowledge of reproductive health with sexual behavior in adolescents at SMA negeri 1 Baturaden class XI. This study uses a type of correlation analytic research with quantitative design and crosssectional approach, samples and non-probability sampling techniques as many as 103 people with Spearman's Rank analysis. The results of this study indicate a significant relationship between the level of reproductive health knowledge and sexual behavior in adolescents with a p value of 0.001 (p <0.05). Indicates a significant relationship between the level of reproductive health knowledge and sexual behavior in adolescents.